EVALUATION OF LIVER FUNCTION IN HORSES WITH DUODENITIS-PROXIMAL JEJUNITIS Avaliação da função hepática em equinos com duodeno-jejunite proximal - Stocco Betiol, Patrícia; dos Santos Michima, Lilian Emy; Fernandes, Wilson Roberto (Revista Acadêmica Ciência Animal, 2012)
Previous reports of duodenitis-proximal jejunitis (DPJ) have noted histopathologic changes in the liver. However, there have been few studies evaluating the hepatic function during the process of DPJ in horses. The objective of this study was to investigate the hypotheses that there is a correlation between DPJ and hepatic dysfunction. Blood samples from 8 horses with DPJ were collected for aspartate aminotransferase (AST), gama-glutamyl transferase (GGT), total (TB), direct (DB) and indirect bilirubin (IB), total serum protein and albumin analysis. The blood samples were collected from horses that survived on the moment of admission at the veterinary hospital, at the time of nasogastric reflux (NGR) end, and at the time the animals were allowed to eat. At the same time, heart rate, respiratory rate, rectal temperature and packed cell volume (PCV) were performed and the volume and duration of NGR were evaluated. Blood samples and parameters of horses that have died were collected at the moment of admission at the hospital. The values of respiratory rate, rectal temperature, volume of NGR, AST, GGT, total protein and albumin were not statistically significant during the trial. By the time of admission at the hospital, the values of heart rate and PCV were significantly greater in horses that have died compared to the survivors. In the survivors there were significant values for heart rate, PCV and for bilirubins. This study did not confirm the hypothesis that DPJ causes hepatic dysfunction in horses when serum biochemical analyses were performed.